Patterns of language errors in the writing of Bosnian EFL students: A case study - Rizvi-Eminovi, Edina; Burekovi, Melisa; Dervic, Mersad (Universitas Syiah Kuala, 2025)
Linguistic errors remain a persistent challenge for B2-level EFL learners, with research showing that grammatical misapplication accounts for nearly half of the language inaccuracies. This study investigates 942 errors in argumentative essays written by Bosnian EFL learners, focusing on grammatical, lexical, and typographical challenges that impact their English writing proficiency. The data, consisting of 90 essays with a total word count of 45,786, were collected and analyzed following a structured procedure: collection, identification, description, and evaluation of learners errors. A descriptive-qualitative error analysis approach was employed to classify errors and examine their underlying causes systematically. To ensure reliability and consistency in the analysis, three instructors independently reviewed the essays. Inter-rater reliability was achieved through collaborative discussions, where any discrepancies in error classification were resolved through consensus. Errors were categorized into grammatical (50.2%), word-choice (29.3%), and typographical (20.5%) types and further analyzed to determine their origins as intralingual or interlingual. A deeper investigation revealed that 58% of errors were intralingual, resulting from overgeneralization and rule misapplication, while the remaining 42% were interlingual, influenced by Bosnian language interference. These findings highlight the need for focused interventions, particularly in grammar and vocabulary instruction. By uncovering error patterns and their causes, the study contributes to refining pedagogical strategies that support EFL learners writing proficiency.